WATER-BASED HYDRO-GEOSYNERGETIC BIOGENIC-MANTLE HYPOTHESIS OF HYDROCARBON FORMATION AND ITS ROLE IN SUBSTANTIATION OF SEARCH TECHNOLOGY - Bagriy, I.D. (Institute of Geological Sciences, NAS of Ukraine, 2016)
As part of matter cycle in nature the hydro-geosynergetic biogenic-mantle hypothesis of hydrocarbon formation was developed and based on it the search structural-thermal-atmo-hydro-geochemical technology (STAHGT) was created. This technology was first carried out and successfully implemented in the process of forecasting and prospecting for oil and gas facilities in Ukraine on land (Dnieper Donets depression) and the Black Sea (the north-western and northeastern shelf) using specially designed equipment complexes. The sources of recovery of hydrocarbon fields in operation were substantiated for the first time.